Current hydrobiological and radioecological state of the Chernobyl NPP cooling pond - Gudkov, D. I.; Protasov, А. А.; Scherbak, V. I.; Dyachenko, T. N.; Kaglyan, А. Е.; Sylaieva, А. А.; Pashkova, O. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
During 2012–2013, the research of the qualitative and quantitative compositions of macrophyte, phyto- and zooplankton, phyto- and zooperiphyton, zoobenthos, and fish communities of the Chernobyl NPP cooling pond was conducted. The levels of radioactive contamination and the assessment of single radionuclide stocks in the main components of the cooling pond’s ecosystem in the period preceding its decommissioning are analyzed.